2016
DOI: 10.1097/rlu.0000000000001340
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT False-Positive Tracer Uptake in Paget Disease

Abstract: 65-year-old man with left-sided pelvic pain on evaluation was found to have features suggestive of either Paget disease or prostatic bone metastasis of the left hemipelvis based on Tc-MDP bone scan and MRI. Ga-PSMA PET/CT to assess the possibility of primary prostate cancer and if present to stage it helped to rule out prostate cancer because of absence of focal abnormal increased tracer uptake in the prostate gland. However, false-positive tracer uptake was noted in the left hemipelvis, which was subject to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…A single case study (Table 2) showed intense 68 Ga-PSMA uptake in skeletal regions that appeared to represent Paget's disease, which was confirmed by biopsy (Sasikumar et al, 2016). This case illustrates recent findings (published after the literature search for the present review) that PSMA is expressed in several tissues other than the prostate, such as in the neovasculature of several tumours, for example myeloma (Rauscher et al, 2017), renal cell carcinoma (Rhee et al, 2016a;Zacho et al, 2017).…”
Section: Pitfalls Of 68 Ga-psma Pet/ct In Bone Imagingsupporting
confidence: 79%
See 3 more Smart Citations
“…A single case study (Table 2) showed intense 68 Ga-PSMA uptake in skeletal regions that appeared to represent Paget's disease, which was confirmed by biopsy (Sasikumar et al, 2016). This case illustrates recent findings (published after the literature search for the present review) that PSMA is expressed in several tissues other than the prostate, such as in the neovasculature of several tumours, for example myeloma (Rauscher et al, 2017), renal cell carcinoma (Rhee et al, 2016a;Zacho et al, 2017).…”
Section: Pitfalls Of 68 Ga-psma Pet/ct In Bone Imagingsupporting
confidence: 79%
“…However, the DTA was performed for bone assessment in only one study. However, in that study, the CT was suggestive of Paget's disease of the bone, which was confirmed by biopsy (Sasikumar et al, 2016). First, the authors concluded that if a 68 Ga-PSMA PET/CT had been performed, a BS would not be needed, and second, they found 68 Ga-PSMA PET/CT to be superior to BS particularly in primary staging and in biochemical recurrence (Pyka et al, 2016).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, these promising agents do not detect all recurrences (5,7), and other types of cancer also express PSMA (8,9). False-positive findings have also been reported using PSMA agents (10)(11)(12). Given the widespread adoption of PSMA radiopharmaceuticals and their excellent performance at all stages of PCa, is there a need or a role for another class of PET radiopharmaceutical targeting other biologic processes in PCa?…”
mentioning
confidence: 99%